Nitrogen-Doped Ketjenblack Carbon Supported Co3O4 Nanoparticles as a Synergistic Electrocatalyst for Oxygen Reduction Reaction - Cheng, Gao; Liu, Guanliang; Liu, Peng; Chen, Liya; Han, Shengbo; Han, Jiaxi; Ye, Fei; Song, Wei; Lan, Bang; Sun, Ming; Yu, Lin (Frontiers in Chemistry, 2019)
Developing highly active and cost-effective cathode electrocatalyst with strong stability for oxygen reduction reaction (ORR) is extremely necessary. In this work, we reported a facile synthetic path to prepare a hybrid nanostructure formed of nitrogen-doped Ketjenblack carbon (N-KC) supported Co3O4 nanoparticles (Co3O4/N-KC), which could be used as a promising and stable electrocatalyst for ORR. Compared with the physical mixture of Co3O4 and N-KC and pure N-KC samples, the resulting Co3O4/N-KC nanohybrid afforded remarkably superb ORR activity with a half-wave potential of 0.82 V (versus reversible hydrogen electrode, RHE) and a limiting current density of 5.70 mA cm-2 in KOH solution (0.1 M). Surprisingly, the Co3O4/N-KC sample possessed a similar electrocatalytic activity but better durability to the 20 wt% Pt/C catalyst. The remarkable ORR activity of Co3O4/N-KC nanohybrid was mainly due to the strong coupling effect between Co3O4 and N-KC, N species dopant, high electroconductivity and large BET surface area. Our work enlightens the exploitation of advanced Co3O4/carbon hybrid material alternative to the Pt-based electrocatalysts.